Comprehensive review of Plasmodiophora brassicae: pathogenesis, pathotype diversity, and integrated control methods - Xu, Xueliang; Wu, Caiyun; Zhang, Fan; Yao, Jian; Fan, Linjuan; Liu, Zirong; Yao, Yingjuan (Frontiers in Microbiology, 2025)
Clubroot disease is an important disease of cruciferous crops worldwide caused by Plasmodiophora brassicae. The pathogen P. brassicae can infect almost all cruciferous crops, resulting in a reduction in yield and quality of the host plant. The first part of this review outlines the process of P. brassicae infestation, effectors, physiological pathotypes and identification systems. The latter part highlights and summarizes the various current control measures and research progress on clubroot. Finally, we propose a strategic concept for the sustainable management of clubroot. In conclusion, this paper will help to deepen the knowledge of P. brassicae and the understanding of integrated control measures for clubroot, and to lay a solid foundation for the sustainable management of clubroot.